Kingdom of bones [compact disc, unabridged] : a thriller - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2022)
"A United Nations relief team in a small village in the Congo makes an alarming discovery. An unknown force is leveling the evolutionary playing field. Men, women, and children have been reduced to a dull, catatonic state while the plants and animals around them have grown more cunning and predatory, evolving at an exponential pace. The insidious phenomenon is spreading across the African continent, threatening the rest of the world. What has made the biosphere run amok? Is it a natural event? Or more terrifyingly, did someone engineer it?"--